Analisis Pembuktian Alasan Pembelaan Terpaksa Yang Melampaui Batas Dalam Tindak Pidana Yang Menyebabkan Kematian - Dewa Agung Ari Aprillya Devita Cahyani; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Jurnal Analogi Hukum, 2019)
Criminal act often occur in Indonesia but not all criminal act can be subject to criminal law. Nooweer is one of the reason of criminal obliteration in criminal code section 49. The problem is how is the forced defence or forced plea creteria to be the cause for criminal obliteration? What is judge’s fundamental consideration in the judgement number 201/Pid.b/2013/PN-JTH and 57 PK/PID/2013?. The research is normative type, in which the assesment is based on law materials from literature and is a process to find the rule of law, legal principles, also legal doctrines. Law material source used in this undergraduate thesis is secondary law material which is the law materials that are obtained throught library research. The conclusions in this research are noodweer has specially arranged in criminal code section 49. In deciding, a judge must consider person worthiness or appropriateness based on evidences and strong judgement.